Making value a priority: how this paradigm shift is changing the landscape in health care. Issue 1 (6th September 2016) - Kimberly, John; Cronk, Imran
Abstract : The world of health care is changing dramatically, as reflected in the number, magnitude, and scope of innovative new approaches—to how illness is treated and how better health is promoted—that are being implemented around the globe. The changes triggered by these initiatives affect both how care is organized, managed, and paid for and the kinds of approaches that are being developed to keep people healthy. Underlying these changes is a more fundamental paradigm shift, a shift in the priority given to "value" in the formulation of policy and management practice. This brief essay highlights five trends that are central in this shift: increasing emphasis on health promotion, movement toward value‐based payment, advances in digital/mobile technology, exploitation of big data, and changes in support for biomedical research. Each of these has its own value controversies, and the individual impact of each is impossible to predict. Collectively, however, their impact is likely to be significant.